In Pursuit of Genuine Chinese Equivalents: The Case of a Nineteenth-Century Dutch-Chinese Dictionary. - Heijns, Audrey (International Journal of Lexicography, 2020)
Despite the consensus among scholars that it is impossible for equivalence to have the same meaning in linguistics as it does in mathematics – it is impossible to have equivalents in translation – there is still merit in investigating bilingual dictionaries as they can help us understand the different gradation and distinct types of equivalence and thus illustrate the problems that compilers faced. As a case study, this paper examines Gustaaf Schlegel's Dutch–Chinese dictionary, with occasional comparison to other dictionaries from the nineteenth century, in order to reconstruct Schlegel's aim of 'genuine Chinese equivalents'. Findings show that, in many instances, Schlegel is skilful in providing cognitive, explanatory or translational equivalents in terms of meaning and function, while providing useful information about the Chinese language and culture. Yet, in some cases, his attempts to find his so-called genuine equivalent fail, because he would not resort to the coining of new words, as other compilers did in that era.